Tahlil al-Akhtha’ al-Lughawiyyah fi Maharah al-Kitabah li Thullab Syu’bah al-Lughah al-‘Arabiyyah wa Adabiha / Analysis of Linguistic Errors in the Writing Skill of Students of the Arabic Language and Literature Study Program - Fikriyah Mahyaddin; Hamzah Hamzah; Zulaeha Zulaeha (Universitas Islam DDI AGH Abdurrahman Ambo Dalle Polewali Mandar, Sulawesi Barat, 2024)
This research aims to find out the forms of language errors in the writing Arabic of second semester students of the Arabic Language and Literature Study Program at State Islamic College of Majene, to find out the causes of language errors in the writting Arabic of second semester students of the Arabic Language and Literature Study Program at State Islamic College of Majene, to know the lecture’s effort to avoid of language errors in the writting Arabic of second semester students of the Arabic Language and Literature Study Program at State Islamic College of Majene. This research method is qualitative research. Researcher used observation, interviews, and documentation as data collection methods. The research population was maharah kitabah lectures and second semester students of the Arabic Language and Literature Study Program at State Islamic College of Majene. Data analysis steps by include data collection, data reduction, data presentation, and drawing conclusions. The research results showed that language errors in the writing of Level II students of the Arabic Language and Literature Study Program at the Majene State Islamic College consisted of nahwu, sharaf, semantic and lexical errors. Factors that cause these errors are students having difficulty in applying the rules of nahwu and sharf, lack of vocabulary, difficulty in writing, especially in describing something, and students being afraid and anxious about describing writing. Efforts made by lecturers include: Encouraging students to write Arabic, participating with students when analyzing mistakes, providing continuous training related to the use of Arabic language rules, and implementing various strategies in learning of Mahara al-Kitabah.المستخلص: يهدف هذا البحث إلى معرفة أشكال الأخطاء اللغوية في كتابة الطلاب المستوى الثاني شعبة اللغة العربية وآدبها بالجامعة الإسلامية الحكومية ماجيني، ومعرفة أسباب الأخطاء اللغوية في كتابة الطلاب المستوى الثاني شعبة اللغة العربية وآدبها بالجامعة الإسلامية الحكومية ماجيني، ومعرفة محاولات المحاضر لتجنب الأخطاء اللغوية في كتابة الطلاب المستوى الثاني شعبة اللغة العربية وآدبها بالجامعة الإسلامية الحكومية ماجيني. ومنهج هذا البحث هو البحث الكيفي. واستخدمت الباحثة الملاحظة، والمقابلة، والتوثيق كطرق لجمع البيانات. أما مجتمع البحث هو محاضر مهارة الكتابة وطلاب المستوى الثاني شعبة اللغة العربية وآدبها بالجامعة الإسلامية الحكومية ماجيني. وخطوات تحليل البيانات من خلال جمع البيانات، وتخفيض البيانات، وعرض البيانات، واستخلاص النتائج. دلت نتائج من هذا البحث أن الأخطاء اللغوية في كتابة الطلاب المستوى الثاني شعبة اللغة العربية وآدبها بالجامعة الإسلامية الحكومية ماجيني تتكون من المستوى النحوي والصرفي والإملائي والمعجمي. ومن العوامل التي تسبب هذه الأخطاء هي الصعوبة في تطبيق القواعد النحوية والصرفية، وقلة المفردات، والصعوبة في الكتابة خاصة في وصف الأشياء والتعبير، وخوف وقلق الطلاب من التعبير. ومن المحاولات التي قدمها المحاضر هي: تشجيع الطلاب في الكتابة، ومشاركة الطلاب عند تحليل الأخطاء، إعطاء التدريبات المستمرة على مهارة الكتابة المقرونة بالقواعد النحوية وقواعد الإملاء، وتنويع استراتيجيات في تعليم مهارة الكتابة.